STATUS HUKUM HIBAH MU'ALLAQAH BI AL-MAUT ANALISIS KOMPARATIF FIKIH EMPAT MAZHAB - Yusdi Haq; Muhammad Tsalis Ramadlani; Oki Anggara Saputra; Azfar ihsanu naufal (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study examines the legal status of conditional hibah specifically, gifts that are stipulated to be received only after the donor’s death based on the analysis of the four major Sunni schools of Islamic jurisprudence. The research is motivated by the widespread practice of conditional hibah in Muslim communities, which is often confused with the concept of wasiyyah (bequest). This study employs a qualitative method using a normative-comparative approach and library research, drawing from primary sources such as classical fiqh texts and secondary literature including academic journals and scholarly works. The findings reveal that hibah is a transfer-of-ownership contract that must take effect during the donor’s lifetime, making immediacy (tanjīz) and certainty of ownership essential for its validity. The majority of jurists reject conditional hibah because it contradicts the nature of hibah as an immediate act of giving, whereas some scholars, such as Ibn Taymiyyah and Ibn al-Qayyim, permit it when the condition is clear and does not contravene Islamic principles. The study also shows that most jurists require qabd (physical possession) as a condition for the completion of hibah. Furthermore, a hibah conditioned upon the donor’s death is invalid as hibah and instead becomes a wasiyyah, subject to the rules of bequests, including the prohibition of bequeathing to heirs unless all other heirs consent. These findings highlight the importance of public awareness regarding the distinction between hibah and wasiyyah to prevent legal disputes